Arterial Doppler Waveforms Are Independently Associated With Maximal Walking Distance in Suspected Peripheral Artery Disease Patients - Miossec, Annaïg; Tollenaere, Quentin; Lanéelle, Damien; Guilcher, Antoine; Métairie, Antoine; Le Pabic, Estelle; Carel, Awenig; Le Faucheur, Alexis; Mahé, Guillaume (Frontiers in Cardiovascular Medicine, 2021)
Objective: Arterial Doppler waveform recordings are commonly used to assess lower extremity artery disease (LEAD) severity. However, little is known about the relationship between arterial Doppler waveform profiles and patients walking capacity. The aim of this study is to assess whether arterial Doppler waveforms are independently associated with the maximal walking distance (MWD) of patients with exertional limb symptoms. Materials and methods: This is a cross-sectional study including patients with exertional limb symptoms suspected of LEAD. Arterial Doppler waveforms and ankle-brachial index (ABI) were acquired on both lower extremities at the pedis and tibial posterior arteries. Each arterial flow was classified using the Saint-Bonnet classification. A treadmill test (3.2 km/h, 10% slope) coupled with exercise oximetry was used to determine the MWD. Following treadmill test, post-exercise ABI were measured. The Delta from Rest Oxygen Pressure (DROP ) was calculated. Univariate and multivariate analyses were used to determine the clinical variables associated with the MWD. Results: One hundred and eighty-six patients (62+/-12 years and 26.8+/-4.5 kg/m2) with exertional limb symptoms were included from May 2016 to June 2019. Median [25th; 75th] MWD on treadmill was 235[125;500]m. The better the arterial Doppler waveforms the better the walking distance (p=.0012). In the group with the best Doppler waveforms, median MWD was 524 [185;525]m whereas median MWD was 182[125,305]m in the group with the worse Doppler waveforms (p= .0039). The patients with the best ABI have a significant better MWD. However, in the multivariate model, only the Arterial Doppler waveforms were significantly associated with the MWD (p= .0009). When exercise variables (Post-exercise ABI or DROP) were added in the multivariate model, only exercise variables were associated with the MWD. Conclusion: Doppler flow waveforms profile is a significant and independent predictor of MWD in patients suffering from exertional limb symptoms.